Prediction of the Central Indian Ocean Mode in S2S Models - Jianhuang Qin; Lei Zhou; Lei Zhou; Baosheng Li; Ze Meng (Frontiers in Marine Science, 2022)
Prediction of precipitation during the Indian summer monsoon (ISM) is a persistent scientific challenge. The central Indian Ocean (CIO) mode was proposed as a subseasonal climate mode over the tropical Indian Ocean, and it has a close relation with monsoon intraseasonal oscillations (MISO) during the ISM both in observations and simulations. In this study, the prediction skill of the CIO mode in the subseasonal-to-seasonal (S2S) air–sea coupled models is examined. The ECMWF and UKMO models display significantly higher skills for up to about 2 and 3 weeks, respectively, which are longer than other S2S models. The decline of the CIO mode prediction skill is due to the reduced signal of subseasonal zonal winds at 850 hPa over the tropical central Indian Ocean (especially along the equator; 5°S–5°N, 70°E–85°E). Therefore, a better simulation of tropical subseasonal zonal winds is required to improve the CIO mode prediction in models, and the improvement will benefit a better MISO simulation and a higher prediction skill during the ISM.